Letter (copy) : re the Secretaryship of the Ophthalmic Benefit Approved Committee - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0024-001 4 Aberdare Gardens, Hampstead, London, N.W.11. 2nd February, 1940. Mr. J.W. Bowen, 1 & 3 London Road, CHERTSEY. Dear Mr. Bowen, re the Secretaryship of the Ophthalmic Benefit Approved Committee. I am writing to you with reference to the above post, as I am informed that a friend of mine, a Mr. George Jeger, a brother of Dr. S. Jeger, L.C.C. (Shoreditch), is applying for the post. Mr. George Jeger was for two years and more the Organising Secretary of the Spanish Medical Aid Committee under my Chairmanship, and I can assure you that the work he did there, combined with his keenness and energy and his ability for organisation was splendid. If you can do anything to help him to secure this appointment I will be very much obliged. Last year he was the Mayor of Shoreditch. I am sending a similar letter to Mr. George Canter, and I would be glad if you would consult with him to see if it is possible for you and other members of the Committee to consider Mr. Jeger's application with favour. You know how seldom I recommend anyone for appointment, unless I am absolutely sure of my ground from the point of view of sobriety, honesty and keenness to work. I do not know whether I am right in approaching you as a Member of the Committee in this, but the advertisement made no mention whatever of canvassing. I would not like to do Mr. Jeger's application any harm by my approach to you, but on the contrary hope that with good intentions it may turn the scales in his favour. Yours sincerely, and with many thanks, 292C/946/2/24